2019
DOI: 10.1108/imefm-01-2018-0029
|View full text |Cite
|
Sign up to set email alerts
|

Mediating effect of intrinsic motivation on the relationship between Islamic work ethic, job satisfaction, and organizational commitment in banking sector

Abstract: Purpose In line with the general purpose mentioned, this paper aims to determine the impact of the Islamic work ethic (IWE) on job satisfaction and organizational commitment among the employees of Bank Maskan by examining the mediating role of intrinsic motivation. Design/methodology/approach Analysis of data obtained from 220 questionnaires related to research variables with AMOS software shows a positive and significant relationship between IWE and job satisfaction and organizational commitment with the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
132
2
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(160 citation statements)
references
References 89 publications
15
132
2
11
Order By: Relevance
“…So it can be concluded that the stronger intrinsic motivation of the Campus Dawah Association administrators will affect increasing their organizational commitment. These results similar to the research by Gheitani et al(2018); Yousaf et al (2014);and Imran, et al (2016). "Interest in work" is an indicator of intrinsic motivation with the highest average value.…”
Section: The Influence Of Psychological Empowerment On Intrinsic Motisupporting
confidence: 90%
See 3 more Smart Citations
“…So it can be concluded that the stronger intrinsic motivation of the Campus Dawah Association administrators will affect increasing their organizational commitment. These results similar to the research by Gheitani et al(2018); Yousaf et al (2014);and Imran, et al (2016). "Interest in work" is an indicator of intrinsic motivation with the highest average value.…”
Section: The Influence Of Psychological Empowerment On Intrinsic Motisupporting
confidence: 90%
“…In addition, it was also found that psychological empowerment had a significant effect on intrinsic motivation (Zhang and Bartol, 2010;Brooks and Young, 2011;Fook et al 2011). In addition to this, intrinsic motivation can also influence organizational commitment (Gheitani, et al 2018;Yousaf et al 2014;Imran et al 2016). Based on the studies mentioned above, the hypothesis is formulated as follows: H 1 : Psychological empowerment has a significant effect on organizational commitment H 2 : Psychological empowerment has a significant effect on intrinsic motivation H 3 : Intrinsic motivation has a significant effect on organizational commitment…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Numerous studies have found that the IWE is closely associated with job satisfaction, e.g. Mohamed, Karim, and Hussein (2010), Yousef (2000), Yousef (2001), Rokhman and Omar (2008), Rokhman (2010), Marri, Sadozai, Zaman, and Ramay (2012), Komari and Djafar (2013), and Gheitani, Imani, Seyyedamiri, and Foroudi (2018). With these arguments, IWE's adoption is required in business operations to bring positive results including job satisfaction.…”
Section: H1 Iwes Is Significantly Related To Organizational Commitmentmentioning
confidence: 99%